High dependency unit patients’ satisfaction from health care provided - Apostolou, Eleni; Papageorgiou, Dimitrios; Dokoutsidou, Eleni (Health & Research Journal, 2016)
Introduction: Patient satisfaction, while influenced by many factors, is a multidimensional phenomenon, which could be used to optimize the quality of the services provided by hospitals, as well as in the patient-centered care. Aim: The aim of the present study was to explore High Dependency Unit (HDU) patients’ satisfaction from health care provided. Material and Method: The studied sample consisted of 101 HDU patients of a general hospital in Attica. Data collection was conducted through the questionnaire of Inpatient Survey Questionnaire, which included demographic data as well as questions relevant to the hospitalization characteristics. Data analysis was performed by the statistical package SPSS ver.22. Results: Patients were satisfied both by the general hospital provisions and staff. A statistically significant difference (t(99) = 2,69 , p = ,008) was found between the subscale “Room” with the majority of men to score higher these services (Μ = 3,83, Τ.Α. = 0,34) compared to women (Μ = 3,65, Τ.Α. = 0,35). Men also scored higher (t(97) = 2,40 p = ,018) the subscale “nursing staff” (Μ = 4,30, Τ.Α. = 0,21) ) compared to women (Μ = 4,17, Τ.Α. = 0,32). A statistically significant difference (t(99) = 2,37, p = ,020) was found between the subscale “food” with the majority of older patient to score higher these services (Μ = 4,06, Τ.Α. = 0,36) than the youngest patients (Μ = 3,88, Τ.Α. = 0,39). Conclusions: Patient satisfaction is a vital factor for optimizing hospital services, is influenced by multiple factors and needs further research so that there will be effective strategies which will focus on optimizing the degree at which patients’ needs are met.